The Influence of Self Efficacy and Social Support on Career Adaptability in Workers with Disability in Bandung - Nugroho, Geski Widiyanto; Sakti, Intan Widuri (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to determine the effect of Self efficacy and Social support on Career adaptability in workers with disabilities in Bandung City. The research method used in this research is a quantitative approach. The population in this study were workers with disabilities in Bandung City. The sampling technique uses an approach from Haier, the number of samples is determined 5 - 10 times the number of questionnaire questions where in this study the questions used totaled 34 questions, if multiplied by 5, the respondents totaled 170 respondents. While the data collection technique uses a questionnaire distributed to employees. The data analysis technique used in this research is multiple linear regression analysis, coefficient of determination, T test and F test with the help of the SPSS program. The results of this study indicate that the Self Efficacy variable has a significant effect on Career Adaptability and Social Support has no significant effect on Career Adaptability.